Spirometric and ergospirometric evaluation of wheelchair rugby players - Domaszewska, Katarzyna; Szymczak, Łukasz; Kryściak, Jakub; Pospieszna, Barbara; Laurentowska, Maria (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Cervical spinal cord injury is one of most common human body deficiencies. Quadriplegia affects not only the mass of paralyzed muscles, but also disrupts physiological exercise adaptation mechanisms. One of the few sports suitable for individuals with cervical spine impairment is wheelchair rugby. Professional athletes display a higher exercise capacity than untrained people with a similar degree of spinal damage. The reduction of aerobic capacity in individuals with cervical spinal cord injury is multifactorial. In addition to cardio-pulmonary mechanisms limiting the exercise capacity, the decrease in active muscle mass leads to the rapid development of tissue hypoxia. Material and Methods. 14 members of the Polish National Wheelchair Rugby Team were recruited for the study. The male players aged 20-40 years with cervical spinal cord in juries underwent spirometric and ergospirometric tests. Results. The mean values of spirometric parameters were: VC 3.9 ± 0.71 l(71.3% predicted), ERV 0.9 ± 0.33 l (60.7% predicted), VE 12.6± 6.34 4 l/min, Bf 18.3 ± 4.72 l/min, VT 0.7 ± 0.20 l, FVC 4.05 ±0.69 l/min (76.3% predicted), FEV1,0/FVC 92.2 ± 7.10% (113.45%predicted), MVV 141.7 ± 24.59 l/min (97.15% predicted). The mean value of peak oxygen consumption during exercise was1.31 ± 0.30 l/min (17.8 ± 4.99 ml/kg/min) achieved within 11.8± 3.51 min. The mean maximal workload was 42.5 ± 13.99 W. During the test only 10 players reached the anaerobic threshold(AT) intensity. The mean workload at AT was 36 ± 10.62 W, andVO2 max at AT was 0.9 ± 0.26 l/min (15.5 ± 4.17 ml/kg/min).Conclusions. The results of spirometric tests indicate the presence of mild and medium restrictive pulmonary changes in 8 out of the studied players of the Polish National Wheelchair Rugby Team. The physiological parameters obtained during the exercise test indicate a higher aerobic capacity of surveyed athletes in comparison with untrained quadriplegics.
Keywords: quadriplegia; maximal oxygen uptake; ergospirometry; spirometry